Systems of Government in Islamic Countries: The Dynamics of Sharia Law from the Prophetic Period to the Modern Era - Sukardi Sukardi; Muhammad Adib Alfarisi; Riyani Riyani (Justicia Islamica, 2024)
This article explores the forms and systems of government practiced by Islamic states from the time of the Prophet to the present day. This research departs from the problem of the debate on the relationship between religion and the state in the practice of Muslim countries that form the diversity of Islamic state administration from classical to modern times. This conceptual research is related to classical to contemporary government practices in Muslim countries. This research uses heuristic and philosophical approaches. Based on the research conducted, this study concludes that four factors cause diversity in the implementation of the constitutional state of Islamic countries, namely: 1) there are no specific rules on constitutionalism in Islamic teachings, 2) the centralized and absolute power of the caliph, 3) the growing tradition of the rule of law, and 4) the influence of Western concepts of democracy through international expansion and the expansion of power in the colonial era. This study contributes practically to offering a more adaptive model of interaction and negotiation of diversity-based governance and constitutions of Muslim-majority countries.